The complexity and regulation of repair of alkylation damage to nucleic acids. (4th March 2021) - Tsao, Ning; Schärer, Orlando D.; Mosammaparast, Nima
Abstract: DNA damaging agents have been a cornerstone of cancer therapy for nearly a century. The discovery of many of these chemicals, particularly the alkylating agents, are deeply entwined with the development of poisonous materials originally intended for use in warfare. Over the last decades, their anti-proliferative effects have focused on the specific mechanisms by which they damage DNA, and the factors involved in the repair of such damage. Due to the variety of aberrant adducts created even for the simplest alkylating agents, numerous pathways of repair are engaged as a defense against this damage. More recent work has underscored the role of RNA damage in the cellular response to these agents, although the understanding of their role in relation to established DNA repair pathways is still in its infancy. In this review, we discuss the chemistry of alkylating agents, the numerous ways in which they damage nucleic acids, as well as the specific DNA and RNA repair pathways which are engaged to counter their effects.